Effects of Positive Strengthening on the Crying, Anger, and Jumping Behavior of Autistic Children in Surabaya Private Schools - Yohana Agatha Christina Ongkowidjojo; Herlan Praktikto (Proceedings of The ICECRS, 2020)
This study aims to determine the effect of the use of behavior therapy with behavioristic methods for behavior disorders of children with autism. These behavioral disorders in the form of angry, crying, jumping behavior that appears when attending lessons at school. This research is an experimental type research. The method used is an experimental method with a single research subject or Single Subject Research (SSR). The research design used is Within Subject Design. The subject of the study was a 3-year-old boy in a private school in Surabaya. Data collection techniques through observation checklist of autistic children's behavior, and observation. The results of the analysis show that there is a positive influence on the use of behavioral therapy with positive reinforcement methods for autistic children's behavior disorders in the form of angry, crying and jumping behaviors. The behavior decreased after being given behavioristic therapy (Operant Conditioning) by giving positive reinforcement in the form of praise and hugs. Positive reinforcement is given as a reward each time after the subject has targeted the behavior. The target behavior is angry, crying and jumping when in class. The behavior decreases when the child comes to school to take lessons in class.